Different ways of saying family (Journal of Parents and Teachers, 2025)
The International Year of the Family was declared in 1994 by the UN in order to raise awareness of its value as the foundation of society. It explains that there are various types of families beyond the traditional one (nuclear, single-parent, single-person, childless, extended family, polygamous, cohabiting, etc.). The UN analyses all the changes that have taken place in family structure, increase in divorces, births, births outside marriage, low birth rates, etc.
Keywords: Family, ONU, Types of Family and Diversity.